Promoting human development in India: Costs of inequality - M. H. Suryanarayana; Ankush Agrawal (International Policy Centre for Inclusive Growth (IPC-IG), 2013)
Policy emphasis in Indian economic development planning has always been on 'economic growth with income redistribution'. Such a strategy seeks to exploit the potential of development programmes for poverty reduction and welfare gains by reducing the costs due to inequality in income distribution. The state of Kerala provides an empirical example to show how it is possible to achieve both growth and improved income distribution by human development, which is also acknowledged by the Government of India. The three critical dimensions of human development identified by the UNDP are (i) a long and healthy life; (ii) knowledge; and (iii) a decent standard of living as measured by per capita income. There is ample scope for achieving economic growth, human development and poverty reduction by reducing the extent of inequality in all these three dimensions of human development. Therefore, this study seeks to quantify the loss in human development due to inequalities in these three dimensions across states in India. This is done using the methodology to estimate a new index called the Inequality-adjusted Human Development Index (IHDI) proposed by the UNDP in its Human Development Report for 2010 entitled The Real Wealth of Nations: Pathways to Human Development. The HDI is a measure that summarises average levels of achievements in each of the three dimensions in terms of unit-free scores obtained by normalising their respective measures with reference to exogenous limits called goalposts. To facilitate international comparisons, the UNDP specifies the goalposts in the global context. To contextualise the HDI estimates with reference to feasibility defined by the country's potential, this study has made appropriate revisions to the goalposts with reference to the mainstream states in India. This is done in terms of order-based statistics, since mean-based estimates are misleading when the distributions of variables under review are skewed.(...)
Keywords: 330; Entwicklungsplanung; Einkommensverteilung; Entwicklungsindikator; Indien